«A Tightrope on Fire»: Samuel P. Huntington e il conflitto israelo-palestinese - Cannizzo, Andrea (Politics, 2024)
The essay aims to analyze the political thought of Samuel P. Huntington regarding the Israeli-Palestinian conflict. Unlike those theses that accuse the author of The Clash of Civilizations of an opportunistic lack of interest in the Palestine question, the paper suggests that the prudent choice of not arguing in depth on that issue is motivated more by methodological than political reasons. Huntington’s political ideas will be analyzed using edited and archival material.